Thieme atlas of anatomy :general anatomy and musculoskeletal system - Schünke, Michael; Schulte, Erik.; Schumacher, Udo.; Ross, Lawrence M.; Lamperti, Edward D. (Stuttgart ; New York : Thieme, 2006)
"The THIEME Atlas of Anatomy integrates anatomy and clinical concepts. It features: organized intuitively, with self-contained guides to specific topics on every two-page spread; hundreds of clinical applications integrated into the anatomical descriptions, emphasizing the vital link between anatomical structure and function; beautifully illustrated with expertly rendered digital watercolors, cross-sections, x-rays, and CT and MRI scans; clearly labeled images help you easily identify each structure; summary tables throughout - ideal for rapid review; and with 1,700 newly created illustrations and 100 tables, this work features comprehensive coverage of the musculoskeletal system and general anatomy, in addition to embryology and surface anatomy."--BOOK JACKET.
At head of title: Thieme.
Keywords: Human anatomy